LED preparation method and LED epitaxial wafer

By using laser annealing technology in the LED preparation process to increase the hole concentration and injection efficiency of the p-type GaN layer, the problem of insufficient light output power of yellow-green LEDs is solved and a significant increase in light output power is achieved.

CN114284403BActive Publication Date: 2025-01-21INST OF SEMICONDUCTORS - CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111625701.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-28
Publication Date
2025-01-21
Estimated Expiration
2041-12-28

AI Technical Summary

Technical Problem

The internal quantum efficiency of existing yellow-green LEDs is less than 50%, resulting in insufficient optical output power, which has become an urgent problem to be solved.

Method used

Through the use of suitable intensity laser annealing technology during the preparation of LED, the MG-H key content in the P-type GAN layer is reduced, the MGGA is subject to the main content, and the activation efficiency of the MGGA is subject to Injecting efficiency.

Benefits of technology

A significant improvement of the light output power of LED, and enhancing the radiation composite efficiency of electronic cavities in the quantum trap structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114284403B_ABST
    Figure CN114284403B_ABST
Patent Text Reader

Abstract

The present disclosure provides a method for preparing an LED, comprising: sequentially forming a GaN nucleation layer, an unintentionally doped GaN layer, an n-type GaN layer, a multi-quantum well structure, a p-type AlGaN electron blocking layer, and a p-type GaN layer on a substrate, and then performing a first annealing and a second annealing treatment to obtain a second sample; after photolithography of the surface of the second sample, etching to the n-type GaN layer to form a table to obtain a third sample; after photolithography of the PN electrode of the third sample, evaporating a first metal layer and a second metal layer, stripping off the excess metal layer, and performing a third annealing treatment to obtain a fourth sample, after evaporating a SiO2 layer on the surface of the fourth sample, photolithography of the SiO2 layer to obtain an LED epitaxial wafer. The present disclosure increases the hole concentration of the p-type GaN layer in the LED structure through laser annealing technology, improves the hole injection efficiency, and increases the radiation recombination of electron-hole pairs in the quantum well structure, thereby improving the light output power of the LED.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of microelectronics technology, and in particular to a method for preparing an LED and an LED epitaxial wafer. Background Art

[0002] GaN-based materials include gallium nitride (GaN), aluminum nitride (AlN), indium nitride (InN) and their ternary or quaternary alloys. GaN-based materials have the characteristics of wide bandgap, direct bandgap, high electron saturation velocity, high breakdown electric field and high thermal conductivity, and have many application potentials in optoelectronics and microelectronics.

[0003] GaN-based materials are direct bandgap semiconductor materials. Through the adjustment of appropriate components, the bandgap can be continuously adjusted from 0.7eV (InN) to 6.2eV (AlN), covering the entire visible light range and including part of the ultraviolet and infrared light. Compared with traditional light sources, GaN-based LEDs have the advantages of high efficiency, low price, long life, high modulation bandwidth, good modulation performance, and high response sensitivity. They have been widely used in different fields such as white light illumination, display technology, backlight source, visible light communication, and biomedicine. At present, the internal quantum efficiency of blue LEDs has reached 80%, while the internal quantum efficiency of yellow-green LEDs is less than 50%, and the internal quantum efficiency of red LEDs is less than 30%. Improving the light output power of yellow-green LEDs has become an urgent problem to be solved. Summary of the invention

[0004] In view of this, the main purpose of the present disclosure is to provide a method for preparing an LED, so as to at least partially solve at least one of the above-mentioned technical problems.

[0005] In order to achieve the above-mentioned purpose, as an embodiment of one aspect of the present disclosure, a method for preparing an LED is provided, comprising: sequentially forming a GaN nucleation layer, an unintentionally doped GaN layer, an n-type GaN layer, 10 pairs of multi-quantum well structures, a p-type AlGaN electron blocking layer, and a p-type GaN layer on a substrate, and then performing a first annealing treatment to obtain a first sample; performing a second annealing treatment on the first sample, and then performing a first cleaning to obtain a second sample; performing photolithography on the surface of the second sample, and etching until the n-type GaN layer forms a mesa to obtain a third sample; and photolithography the P of the third sample. After the N electrode, the first metal layer of Cr, Al, Ti, and Au is sequentially evaporated at the first mesa position exposed by the photoresist, and the second metal layer of Cr, Al, Ti, and Au is sequentially evaporated at the second mesa position exposed by the photoresist, then the excess first metal layer and the second metal layer are stripped off, and finally a third annealing treatment is performed to obtain a fourth sample, wherein the first mesa position is lower than the second mesa position; the surface of the fourth sample is firstly evaporated with a SiO2 layer, and then the SiO2 layer is photolithographically processed, and then the excess SiO2 is removed by wet etching, and finally a second cleaning is performed to obtain an LED epitaxial wafer.

[0006] As an embodiment of another aspect of the present disclosure, there is provided an LED epitaxial wafer prepared by the above-mentioned preparation method.

[0007] The LED manufacturing method provided by the above embodiment of the present disclosure increases the hole concentration of the p-type GaN layer in the LED structure through the laser annealing technology of appropriate intensity, improves the hole injection efficiency, and leads to an increase in the radiation recombination of electron-hole pairs in the quantum well structure, thereby improving the light output power of the LED. The reason for the increase in hole concentration is that the laser annealing technology can reduce the content of Mg-H bonds in the p-type GaN layer, increase the Mg Ga Acceptor content; at the same time, due to the higher temperature provided by laser annealing, the Mg Ga The activation efficiency of the acceptor is increased, thereby increasing the hole concentration. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 is a schematic flow chart of a method for preparing an LED according to an exemplary embodiment of the present disclosure;

[0009] Figure 2 is a schematic structural diagram of a fourth sample obtained by a method for preparing an LED according to an exemplary embodiment of the present disclosure; and

[0010] Figure 3 The graphs are the curves of light output power versus current for LED epitaxial wafer 1, LED epitaxial wafer 2, and LED epitaxial wafer 3 prepared in Example 1, Example 2, and Comparative Example 1 of the present disclosure.

[0011] Reference numerals:

[0012] 1- substrate;

[0013] 2-GaN nucleation layer;

[0014] 3- Unintentionally doped GaN layer;

[0015] 4-n-type GaN layer;

[0016] 5-Multi-quantum hydrazine structure;

[0017] 6-p-type AlGaN electron blocking layer;

[0018] 7-p-type GaN layer;

[0019] 8- second metal layer;

[0020] 9-First metal layer. DETAILED DESCRIPTION

[0021] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.

[0022] When the hole concentration of the p-type GaN layer in the GaN-based LED material increases, the hole injection efficiency will increase, which will lead to an increase in the radiative recombination of electron-hole pairs in the quantum well structure, thereby significantly improving the light output power of the LED.

[0023] According to the general inventive concept of one aspect of the present disclosure, a method for preparing an LED is provided, comprising: sequentially forming a GaN nucleation layer, an unintentionally doped GaN layer, an n-type GaN layer, 10 pairs of multi-quantum well structures, a p-type AlGaN electron blocking layer, and a p-type GaN layer on a substrate, and then performing a first annealing treatment to obtain a first sample; performing a second annealing treatment on the first sample, and then performing a first cleaning to obtain a second sample; performing photolithography on the surface of the second sample, and then etching until the n-type GaN layer forms a mesa to obtain a third sample; and photolithography the PN electrode of the third sample. Finally, a first metal layer of Cr, Al, Ti, and Au is sequentially evaporated at the first mesa position exposed by the photoresist, and a second metal layer of Cr, Al, Ti, and Au is sequentially evaporated at the second mesa position exposed by the photoresist, then the excess first metal layer and second metal layer are stripped off, and finally a third annealing treatment is performed to obtain a fourth sample, wherein the first mesa position is lower than the second mesa position; a SiO2 layer is firstly evaporated on the surface of the fourth sample, and then the SiO2 layer is photolithographically processed, and then excess SiO2 is removed by wet etching, and finally a second cleaning is performed to obtain an LED epitaxial wafer.

[0024] The LED manufacturing method provided by the embodiment of the present disclosure reduces the content of Mg-H bonds in the p-type GaN layer and increases the Mg Ga Acceptor content; at the same time, due to the higher temperature provided by laser annealing, the Mg Ga The activation efficiency of the acceptor increases, thereby increasing the hole concentration in the GaN layer and the hole injection efficiency, resulting in an increase in the radiative recombination of electron-hole pairs in the quantum well structure, and finally significantly improving the light output power of the LED.

[0025] Figure 1 It is a schematic flow chart of a method for preparing an LED according to an exemplary embodiment of the present disclosure.

[0026] like Figure 1 As shown, the method for preparing an LED includes operations S001 to S005.

[0027] In operation S001, a GaN nucleation layer, an unintentionally doped GaN layer, an n-type GaN layer, a 10-pair multi-quantum well structure, a p-type AlGaN electron blocking layer, and a p-type GaN layer are sequentially formed on a substrate, and then a first sample is obtained by performing a first annealing treatment.

[0028] According to an embodiment of the present disclosure, the material of the substrate 1 is c-plane sapphire, and the thickness of the c-plane sapphire is 200-900 μm, for example, 230 μm, 260 μm, 280 μm, 300 μm, 330 μm, 360 μm, 390 μm, 430 μm, 460 μm, 500 μm, 530 μm, 560 μm, 590 μm, 660 μm, 720 μm, 780 μm, 830 μm, 880 μm; the thickness of the GaN nucleation layer 2 is the thickness of the unintentionally doped GaN layer 3 is 1 to 5 μm, for example, 2 μm, 3.5 μm, 4 μm, 4.5 μm.

[0029] According to the embodiment of the present disclosure, the thickness of the n-type GaN layer 4 is 1-4 μm, for example, 2 μm, 2.5 μm, 3 μm, and the content of the doped Si element is 1×10 17 ~1×10 19 atom / cm 3 , for example, 1×10 18 atom / cm 3 The epitaxial growth temperature is 1000-1200°C, for example, 1050°C, 1100°C, 1150°C.

[0030] According to an embodiment of the present disclosure, the width of the well in the multi-quantum well structure 5 is 1 to 4 nm, for example, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, and the width of the quantum barrier is 9 to 20 nm, for example, 9.5 nm, 10 nm, 12 nm, 16 nm, 18 nm; the In content in the well part of the multi-quantum well structure 5 is 10 to 30%, for example, 12%, 13%, 16%, 18%, 22%, 26%, 28%, and the In content in the quantum barrier part is 0 to 10%, for example, 2%, 3%, 6%, 8%, 9%.

[0031] According to the embodiment of the present disclosure, the thickness of the p-type AlGaN electron blocking layer 6 is 10-50 nm, for example, 12 nm, 16 nm, 22 nm, 28 nm, 32 nm, 36 nm, 42 nm, 48 nm, and the content of the doped Mg element is 1×10 17 ~1×10 19 atom / cm 3 , for example, 1×10 18 atom / cm 3 The epitaxial growth temperature is 900-1100°C, for example, 930°C, 950°C, 980°C, 1030°C, 1080°C, and the carrier gas is hydrogen; the thickness of the p-type GaN layer 7 is 0.2-2 μm, for example, 0.4 μm, 0.6 μm, 0.8 μm, 1.2 μm, 1.4 μm, 1.8 μm, and the content of the doped Mg element is about 1×10 19 ~5×10 20 atom / cm 3 , for example, 2×10 20 atom / cm 3 , 3×10 20 atom / cm 3 , 4×10 20 atom / cm 3 The epitaxial growth temperature is 900-1100° C., for example, 910° C., 930° C., 940° C., 960° C., 1040° C., 1080° C., and the carrier gas is hydrogen.

[0032] According to an embodiment of the present disclosure, the conditions for the first annealing treatment are: in a nitrogen atmosphere, the temperature is 500-1000°C, for example, 560°C, 630°C, 720°C, 810°C, 940°C, 980°C, and the time is 10-60min, for example, 12min, 16min, 22min, 24min, 32min, 36min, 42min, 48min, 52min, 58min.

[0033] Operation S002 , after performing a second annealing treatment on the first sample, performing a first cleaning to obtain a second sample.

[0034] According to an embodiment of the present disclosure, the second annealing treatment is a laser annealing treatment, wherein the parameters are set as follows: the laser wavelength of the laser annealing is 200-600nm, for example, 230nm, 290nm, 320nm, 420nm, 580nm, the laser pulse width is 10fs-1ns, for example, 100fs, 1ps, 10ps, 100ps, the laser pulse frequency is 1-1000kHz, for example, 10kHz, 90kHz, 230kHz, 360kHz, 460kHz, 580kHz, 690kHz, 780kHz, 890kHz, the laser scanning rate is 1-10000mm / s, for example, 90mm / s, 1900mm / s, 5900mm / s, 8900mm / s, 9600mm / s, the average laser power is 0-5W, for example, 1.5W, 2.5W, 3.5W, 4.5W, the laser power percentage is 0-100%, for example, 15%, 25%, 35%, 45%, 55%, 65%, 75%, 85%, 95%, the laser spot diameter is 10-1000μm, for example, 120μm, 360μm, 480nm, 560μm, 680μm, 780μm, 890μm, 980μm, the laser spot interval is 5-1000μm, for example, 120μm, 230μm, 320μm, 480μm, 560μm, 680μm, 760μm, 890μm, the laser treatment times is 1-10 times, for example, 2 times, 3 times, 5 times, 6 times, 8 times.

[0035] According to the embodiments of the present disclosure, the specific process of the first cleaning is: first, soak in a concentrated hydrochloric acid solution with a volume fraction of 50% for 5 to 15 minutes, for example, 6 minutes, 8 minutes, 11 minutes, 13 minutes, and 14 minutes, then use acetone to ultrasonically perform at 65°C for 5 to 15 minutes, for example, 6 minutes, 8 minutes, 12 minutes, and 14 minutes, and then use anhydrous ethanol to soak for 5 to 15 minutes, for example, 7 minutes, 9 minutes, 11 minutes, and 13 minutes, and finally rinse with deionized water and blow dry with a nitrogen gun.

[0036] In operation S003 , the surface of the second sample is photolithographically processed and then etched until the n-type GaN layer forms a mesa, thereby obtaining a third sample.

[0037] In some embodiments of the present disclosure, the etching method is ICP etching.

[0038] Operation S004, after photolithography of the PN electrode of the third sample, the first metal layer of Cr, Al, Ti, and Au is sequentially evaporated at the first mesa position exposed by the photoresist, and the second metal layer of Cr, Al, Ti, and Au is sequentially evaporated at the second mesa position exposed by the photoresist, then the excess first metal layer and second metal layer are stripped off, and finally a third annealing treatment is performed to obtain the fourth sample.

[0039] In some embodiments of the present disclosure, the first table position is lower than the second table position.

[0040] According to an embodiment of the present disclosure, the thicknesses of the first metal layers Cr, Al, Ti, and Au are 10-20 nm, 0-20 nm, 10-20 nm, and 10-20 nm, respectively. For example, the thicknesses of the first metal layers Cr, Al, Ti, and Au are 12 nm, 14 nm, 15 nm, and 16 nm, respectively, and the thicknesses of the first metal layers Cr, Al, Ti, and Au are 18 nm, 18 nm, 18 nm, and 18 nm, respectively; the thicknesses of the second metal layers Cr, Al, Ti, and Au are 10-20 nm, 0-20 nm, 10-20 nm, and 10-20 nm, respectively. For example, the thicknesses of the second metal layers Cr, Al, Ti, and Au are 11 nm, 13 nm, 17 nm, and 19 nm, respectively, and the thicknesses of the second metal layers Cr, Al, Ti, and Au are 12 nm, 12 nm, 12 nm, and 12 nm, respectively.

[0041] According to an embodiment of the present disclosure, the conditions of the third annealing treatment are: in a nitrogen atmosphere, the temperature is 200-400°C, for example, 230°C, 280°C, 360°C, and the time is 10-60min, for example, 15min, 28min, 36min, 46min, 58min.

[0042] Figure 2 It is a schematic structural diagram of a fourth sample obtained according to a method for preparing an LED according to an exemplary embodiment of the present disclosure.

[0043] like Figure 2 As shown, the positions of the second terrace of the fourth sample are in the order from bottom to top: substrate 1, GaN nucleation layer 2, unintentionally doped GaN layer 3, n-type GaN layer 4, multi-quantum hydrazine structure 5, p-type AlGaN electron blocking layer 6, p-type GaN layer 7, and second metal layer 8; the positions of the first terrace are in the order from bottom to top: substrate 1, GaN nucleation layer 2, unintentionally doped GaN layer 3, n-type GaN layer 4, and second metal layer 8.

[0044] In operation S005, the surface of the fourth sample is firstly subjected to an SiO2 layer evaporated, followed by photolithography of the SiO2 layer, and then to wet etching to remove excess SiO2, and finally to a second cleaning to obtain an LED epitaxial wafer.

[0045] According to an embodiment of the present disclosure, the specific operation of wet etching is: soaking in a hydrofluoric acid solution with a concentration of 30-60% for 30-100s, for example, the concentration is 32%, 38%, 46%, 52%, 58%, and the soaking time is 38s, 46s, 58s, 66s, 78s, 88s, 96s; the specific process of the second cleaning is: first ultrasonic cleaning with SM-15 remover for 10-15min, for example, 11min, 12min, 13min, 14min, then soaking in anhydrous ethanol for 5-10min, for example, 6min, 7min, 8min, 9min, and finally cleaning with deionized water and blowing dry with a nitrogen gun.

[0046] According to an embodiment of the present disclosure, there is also provided an LED epitaxial wafer prepared by the above-mentioned preparation method.

[0047] The present disclosure is further illustrated below by comparative examples and embodiments. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive explanation of the embodiments of the present disclosure. However, it is apparent that one or more embodiments may also be implemented without these specific details. Moreover, in the absence of conflict, the details in the following embodiments may be arbitrarily combined into other feasible embodiments.

[0048] Example 1

[0049] S1: Prepare a 2-inch c-plane sapphire substrate, put the sapphire substrate into a MOCVD furnace (Veeco), raise the temperature to 525°C, set the reaction chamber pressure to 500 Torr, introduce ammonia gas with a flow rate of 15000 sccm, trimethyl gallium gas with a flow rate of 100 sccm, and hydrogen gas with a flow rate of 100 L / min for 2 minutes, and form a GaN nucleation layer 2 with a thickness of 20 nm on the c-plane sapphire substrate 1;

[0050] S2: the temperature is raised to 1000°C, the pressure of the reaction chamber is 400 Torr, ammonia gas with a flow rate of 30000 sccm, trimethyl gallium gas with a flow rate of 500 sccm and hydrogen gas with a flow rate of 100 L / min are introduced, the growth time is 40 minutes, and a non-intentionally doped GaN layer 3 with a thickness of 2 μm is grown on the GaN nucleation layer 2;

[0051] S3: the temperature is raised to 1080° C., the pressure of the reaction chamber is 50 Torr, 50000 sccm of ammonia, 20 sccm of trimethylgallium, 50000 sccm of hydrogen and 500 sccm of silane are introduced for 50 minutes, and a Si-doped n-type GaN layer 4 with a thickness of 3 μm is grown on the unintentionally doped GaN layer 3;

[0052] S4: growing 10 pairs of multi-quantum well structures 5 on the n-type GaN layer 4, wherein the width of the hydrazine in the quantum hydrazine structure is 3 nm, and the width of the quantum barrier is 12 nm; wherein the growth temperature of the quantum well is 710°C, the pressure of the reaction chamber is 200 Torr, 50000 sccm of ammonia, 20 sccm of trimethyl gallium, 1500 sccm of trimethyl indium and 100 L / min of nitrogen are introduced, and the growth time is 1 minute; the growth temperature of the quantum barrier is 850°C, the pressure of the reaction chamber is 200 Torr, the pressure of the reaction chamber is 50000 sccm of ammonia, 50 sccm of trimethyl gallium and 100 L / min of nitrogen are introduced, and the growth time is 5 minutes;

[0053] S5: the temperature is raised to 900° C., the pressure of the reaction chamber is 200 Torr, ammonia gas with a flow rate of 50000 sccm, trimethylgallium gas with a flow rate of 50 sccm, trimethylaluminum gas with a flow rate of 20 sccm, hydrogen gas with a flow rate of 100 L / min, and magnesium cyclopentadienyl gas with a flow rate of 1000 sccm, and the growth time is 2 min, and a p-type AlGaN electron blocking layer 6 with a thickness of 20 nm is grown on the multi-quantum well structure 5;

[0054] S6: raising the temperature to 950°C, the reaction chamber pressure to 200 Torr, introducing ammonia gas with a flow rate of 50000 sccm, trimethylgallium gas with a flow rate of 70 sccm, hydrogen gas with a flow rate of 100 L / min, and magnesium cyclopentadienyl gas with a flow rate of 1000 sccm, growing a p-type GaN layer 7 heavily doped with Mg with a thickness of 300 nm on the p-type AlGaN electron blocking layer 6, and the growth time is 16 minutes, and a first sample is obtained after a first annealing treatment; wherein, the conditions of the first annealing treatment are: in a nitrogen atmosphere, the temperature is 800°C, and the time is 30 minutes;

[0055] S7: Perform the second annealing treatment on the first sample, set the laser parameters: wavelength of 532nm, laser pulse width of 8ps, laser frequency of 100kHz, laser spot size of 50μm, interval of 50μm, laser power of 100mJ / cm 2 , the number of laser treatments is 1. Then the first cleaning is performed: first, soak in a 50% volume fraction concentrated hydrochloric acid solution for 10 minutes, then use acetone to ultrasonicate at 65°C for 10 minutes, then soak in anhydrous ethanol for 10 minutes, finally rinse with deionized water, and blow dry with a nitrogen gun to obtain the second sample;

[0056] S8: After photolithography, the surface of the second sample is subjected to ICP etching until the n-type GaN layer 4 forms a mesa, thereby obtaining a third sample;

[0057] S9: After photolithography of the PN electrode of the third sample, the first metal layers of Cr, Al, Ti, and Au are sequentially vapor-deposited at the first terrace position exposed by the photoresist, wherein the thicknesses of the Cr, Al, Ti, and Au metal layers in the second metal layer are 70nm, 170nm, 50nm, and 200nm, respectively; the second metal layers of Cr, Al, Ti, and Au are sequentially vapor-deposited at the second terrace position exposed by the photoresist, wherein the thicknesses of the Cr, Al, Ti, and Au metal layers in the second metal layer are 70nm, 170nm, 50nm, and 200nm, respectively. Then, the excess first and second metal layers are peeled off. Finally, the third annealing treatment is performed, wherein the annealing treatment conditions are: in a nitrogen atmosphere, at 300°C for 30 minutes to obtain the fourth sample;

[0058] S10: A SiO2 layer with a thickness of 220 nm was evaporated on the surface of the fourth sample, and then the SiO2 layer was photolithographically processed, and then it was immersed in a 50% hydrofluoric acid solution for 80 seconds, and finally it was cleaned for the second time. The specific process was as follows: first, ultrasonically cleaned with SM-15 remover for 10 minutes, and then immersed in anhydrous ethanol for 10 minutes, and finally, cleaned with deionized water and dried with a nitrogen gun to obtain LED epitaxial wafer 1.

[0059] S11: Determine the curve of the light output power of the LED epitaxial wafer 1 obtained in step S10 versus the current. The result is as follows: Figure 3 shown.

[0060] Example 2

[0061] Except for "S8, the laser power is 200mJ / cm 2 ” and “S10 obtains LED epitaxial wafer 2”, the remaining steps are the same as those in Example 1.

[0062] Comparative Example 1

[0063] Except that "there is no step S8" and "the LED epitaxial wafer 3 is obtained in S10", the remaining steps are the same as those in Example 1.

[0064] like Figure 3As shown, at 20 mA, the optical output power of the LED epitaxial wafer 1 prepared in Example 1 is 17% higher than that of the LED epitaxial wafer 3 prepared in Comparative Example 1; at 20 mA, the optical output power of the LED epitaxial wafer 2 prepared in Example 2 is 29.4% higher than that of the LED epitaxial wafer 3 prepared in Comparative Example 1. It can be seen that the optical output power of the LED epitaxial wafer treated by laser annealing is significantly improved.

[0065] The LED manufacturing method provided in the embodiment of the present disclosure reduces the content of Mg-H bonds in the p-type GaN layer and increases the Mg Ga Acceptor content; at the same time, due to the higher temperature provided by laser annealing, the Mg Ga The activation efficiency of the acceptor increases, thereby increasing the hole concentration in the GaN layer and the hole injection efficiency, resulting in an increase in the radiative recombination of electron-hole pairs in the quantum well structure, and finally significantly improving the light output power of the LED.

[0066] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.

Claims

1. A method for preparing an LED, characterized in that: include: After sequentially forming a GaN nucleation layer (2), an unintentionally doped GaN layer (3), an n-type GaN layer (4), 10 pairs of multi-quantum well structures (5), a p-type AlGaN electron blocking layer (6), and a p-type GaN layer (7) on a substrate (1), a first sample is obtained by performing a first annealing treatment; After performing a second annealing treatment on the first sample, performing a first cleaning to obtain a second sample; After photolithography is performed on the surface of the second sample, etching is performed until the n-type GaN layer (4) forms a mesa, thereby obtaining a third sample; After photolithography of the PN electrode of the third sample, a first metal layer of Cr, Al, Ti, and Au is sequentially evaporated at the first mesa position exposed by the photoresist, and a second metal layer of Cr, Al, Ti, and Au is sequentially evaporated at the second mesa position exposed by the photoresist, then the redundant first metal layer and the second metal layer are stripped off, and finally a third annealing treatment is performed to obtain a fourth sample, wherein the first mesa position is lower than the second mesa position; The surface of the fourth sample is first subjected to evaporation of a SiO2 layer, then subjected to photolithography of the SiO2 layer, and then subjected to wet etching to remove excess SiO2, and finally subjected to a second cleaning to obtain an LED epitaxial wafer; The second annealing treatment is a laser annealing treatment, and the second annealing treatment increases the hole concentration of the p-type GaN layer in the LED to improve the hole injection efficiency and increases the radiation recombination of electron-hole pairs in the quantum well structure, thereby improving the light output power of the LED; Among them, the parameters of the second annealing treatment are set as follows: the laser wavelength of the laser annealing is 200~600nm, the laser pulse width is 10fs~1ns, the laser pulse frequency is 1~1000 kHz, the laser scanning rate is 1~10000 mm / s, the laser average power is 0~5 W, the laser power percentage is 0~100%, the laser spot diameter is 10~1000μm, the laser spot interval is 5~1000μm, and the number of laser treatments is 1~10 times.

2. The preparation method according to claim 1, characterized in that: The material of the substrate (1) is c-plane sapphire, and the thickness of the c-plane sapphire is 200-900 μm; The thickness of the GaN nucleation layer (2) is 15-200 nm; The thickness of the unintentionally doped GaN layer (3) is 1-5 μm.

3. The preparation method according to claim 1, characterized in that: The thickness of the n-type GaN layer (4) is 1-4 μm, and the content of the doped Si element is 1×10 17 ~1×10 19 atom / cm 3 , the epitaxial growth temperature is 1000~1200℃.

4. The preparation method according to claim 1, characterized in that: The width of the well in the multi-quantum well structure (5) is 1-4 nm, and the width of the quantum barrier is 9-20 nm; In the multi-quantum well structure (5), the In content in the well part is 10-30%, and the In content in the quantum barrier part is 0-10%.

5. The preparation method according to claim 1, characterized in that: The thickness of the p-type AlGaN electron blocking layer (6) is 10-50 nm, and the content of the doped Mg element is 1×10 17 ~1×10 19 atom / cm 3 , epitaxial growth temperature is 900~1100℃, and the carrier gas is hydrogen; The p-type GaN layer (7) has a thickness of 0.2-2 μm and a doped Mg content of 1×10 19 ~5×10 20 atom / cm 3 , the epitaxial growth temperature is 900~1100℃, and the carrier gas is hydrogen.

6. The preparation method according to claim 1, characterized in that: The conditions of the first annealing treatment are: in a nitrogen atmosphere, the temperature is 500-1000° C., and the time is 10-60 min; The third annealing treatment is carried out under the following conditions: a nitrogen atmosphere at a temperature of 200-400° C. and a time of 10-60 min.

7. The preparation method according to claim 1, characterized in that The thicknesses of the first metal layers Cr, Al, Ti, and Au are 10-20 nm, 0-20 nm, 10-20 nm, and 10-20 nm, respectively; The thicknesses of the second metal layers Cr, Al, Ti, and Au are 10-20 nm, 0-20 nm, 10-20 nm, and 10-20 nm, respectively.

8. The preparation method according to claim 1, characterized in that: The specific process of the first cleaning is: first, soak in a 50% by volume concentrated hydrochloric acid solution for 5 to 15 minutes, then use acetone to ultrasonicate at 65°C for 5 to 15 minutes, then soak in anhydrous ethanol for 5 to 15 minutes, finally rinse with deionized water, and blow dry with a nitrogen gun.

9. The preparation method according to claim 1, characterized in that: The specific operation of the wet etching is: soaking in a hydrofluoric acid solution with a concentration of 30-60% for 30-100 seconds; The specific process of the second cleaning is: first use SM-15 film remover for ultrasonic cleaning for 10 to 15 minutes, then use anhydrous ethanol to soak for 5 to 10 minutes, and finally use deionized water to clean and blow dry with a nitrogen gun.

10. An LED epitaxial wafer prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nitride luminescent device and production method thereof

    CN101540364A

  • Laser spike annealing for GaN LEDs

    CN102110748A

  • Laser annealing device and laser annealing method used for P type GaN activation

    CN103586580A